Rotator Cuff Tears Are Related to the Side Sleeping Position - David P. Richards, M.D., F.R.C.S.C; Daniel L. Miller, M.D; E. David MacDonald, B.Sc.P.T., M.B.A; Quinn F. Stewart, B.Sc; Stephen D. Miller, M.D., F.R.C.S.C (Elsevier, 2024)
Purpose: To determine whether there was a relationship between sleep position and symptomatic partial- and full-thickness rotator cuff tears. Methods: A consecutive series of patients that met the inclusion/exclusion criteria (n = 58) were in seen in clinic between July 2019 and December 2019. All of these individuals had a significant partial-thickness (> 50%) or full-thickness rotator cuff tear determined by either ultrasound, magnetic resonance imaging, or both. All patients in this series either had an insidious onset of shoulder pain or their symptoms were related to the basic wear and tear of daily activities. Traumatic rotator cuff tears (those associated with a significant traumatic event such as shoulder instability, motor vehicle accidents, sports related injuries, etc.) were excluded. Previous shoulder surgery, recurrent rotator cuff tears, and worker's compensation cases also were excluded from this series. As part of the history-taking process, the patients were asked what was their preferred sleeping position-side sleeper, back sleeper, or stomach sleeper. A χ2 test was conducted to determine the relationship between rotator cuff pathology and sleep position. Results: Of the 58 subjects, 52 of the patients were side sleepers, 4 were stomach sleepers, 1 was a back sleeper, and 1 preferred all 3 positions. Statistical analysis, using the χ2 test (P < .0001), demonstrated that rotator cuff tears were most often seen in side sleepers. Conclusions: In our study, there appeared to be a relationship between the preference of being a side sleeper and the presence of a rotator cuff tear. Level of Evidence: Level IV, prognostic case series.